Frequency of Childhood Mitochondrial Myopathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The frequency of mitochondrial diseases among patients with childhood encephalopathies and myopathies in a defined population of Northern Finland was investigated at the University of Oulu, Finland.